Intersectional inequalities in loneliness among older adults before and during the early phase of the COVID-19 pandemic: A total population survey in the Swedish eldercare setting. (December 2022) - Gustafsson, Per E.; Fonseca-Rodríguez, Osvaldo; Nilsson, Ingeborg; San Sebastián, Miguel
Abstract: Loneliness among older adults is a public health problem that has received particular attention since the emergence of the COVID-19 pandemic. Studies to date have however found a rather modest psychosocial impact of the pandemic on older adults, and scarce research has analyzed this impact using a comprehensive equity lens. The present study used an intersectional approach to examine social inequalities in loneliness before and during the early phase of the pandemic among older adults receiving eldercare in Sweden. The study population (analytical N = 205, 529) came from two waves (2019 and 2020) of a total population survey to all older adult (>65 years of age) home care recipients and nursing home residents in Sweden. Loneliness was self-reported by a single-item measure, and survey data were linked to population register data on age, gender, residential setting, income, and country of birth. Additive binomial regression models were used to estimate prevalence differences and discriminatory accuracy according to an analysis of individual heterogeneity and discriminatory accuracy (AIHDA) approach. Results showed inequalities in loneliness arising particularly in the intersection of country of birth, income, and residential setting. The inequalities widened slightly but ubiquitously following the emergence of the pandemic in 2020, with particularly nursing home residents emerging as a risk group. The discriminatory accuracy of inequalities was consistently low to moderate throughout the analyses but increased marginally during the pandemic in 2020. The study illustrates how social inequalities engenders heterogeneity in the psychosocial risk of older adults before and during the pandemic. These findings should stimulate more nuanced and equity-oriented depictions, research and policies about loneliness among older adults in the peri-pandemic era. Highlights: Prevalence of loneliness among older adults is patterned by complex inequalities. Older adults' country of birth, income and residence matter the most for loneliness. Intersectional inequalities in loneliness increased during COVID-19 pandemic. Nursing home residents were hit particularly hard by the pandemic.